Penggunaan Minyak Biji Feun Kase (Thevetia Peruviana) Sebagai Inhibitor Korosi Logam Seng Dalam Media Asam - Noviana Getrudis Abi; Matius Stefanus Batu; Maria Magdalena Kolo (Saintek Lahan Kering, 2023)
Research on using Feun Kase (Thevetia Peruviana) seed oil as a corrosion inhibitor for zinc metal has been done. This study aims to determine the optimum conditions of immersion time, inhibitor concentration, and temperature in the corrosion inhibition process. Fun Kase seed oil was obtained by maceration extraction for five days using methanol solvent. The inhibition test using the weight reduction method was carried out with variations in immersion time, inhibitor concentration, and temperature to determine the inhibition efficiency and corrosion rate per year in the corrosion test process. From the research results, the optimum immersion time and inhibitor concentration were obtained at 3 hours of immersion time, and a concentration of 1000 ppm with an inhibition efficiency of 43.16% and a corrosion rate of 13.48 mph, and the optimum temperature was obtained at 30ÂºC with an inhibition efficiency value of 21.33 %.